The Somme Chronicles South Africans on the Western Front - Schoeman, Chris; Schoeman, Chris (Penguin Random House South Africa, 2014)
?The heavy smell of blood filled the air, and every moment you had this intense fear that the next bullet was meant for you. So remembered William Thorne, a South African volunteer soldier who fought in the muddy trenches along the River Somme in France on Europe?s Western Front. A boy of nineteen at the time, he was one of thousands of South Africans who took part in the 1916 Somme Offensive between the Allied forces and the Germans. It was one of the bloodiest and costliest conflicts of the First World War, resulting in over a million deaths. The men of the 1st South African Infantry Brigade were involved on a large scale and distinguished themselves in all major engagements during the campaign. But their bravery came at a price. In the first month alone, after six days of fighting to recapture the village of Longueval and clear Delville Wood of enemy soldiers, of the brigade?s 3 433 soldiers, only 750 were left standing. The rest were dead or wounded. By the armistice, the South Africans had suffered some 15 000 casualties in France, of which one third had died.